The Ability and Readiness of Prospective Elementary School Teachers in Facing Digital-Based Learning Era - Adrias; Fitria, Yanti; Ladiva, Hasmai Bungsu; Ruswandi, Agus; Erita, Yeni (International Journal of Elementary Education, 2023)
The Covid 19 pandemic in Indonesia has disrupted the learning process in educational institutions. The impact of this disruption is acceleration in the integration of digital systems in learning, then it creates some problems in network-based learning such as internet connection problems, student participation, and the adaptability of lecturers and students. After the pandemic, network-based or digital learning has become a demand for lecturers and students. This study aimed to analyzed student’s abilities and readiness to participate in digital-based learning after the Covid-19 pandemic. The method of this research is a descriptive research method with data collection techniques in the form of questionnaires and written interviews through online meetings. The sample of this research was 414 students of Elementary School Teacher Education Study Program. The data analysis technique of this research is data reduction, data display and verification. The results of this study indicate that students use Information Technology devices in network-based learning at the capable level, and students’ readiness for digital-based learning after the Covid-19 pandemic is at the ready level. The intensity of students accessing digital teaching materials is very high, but only 5.56% of students have very complete teaching material documents. Student readiness in the aspect of participation in virtual meetings is at the ready level. As many as 53.86% of students consider lectures to be more effective face-to-face (offline). Internet connection quality is an obstacle for students in participating digital-based learning.